PENGARUH MANAJEMEN DISIPLIN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA - IPAH MULYANI IPAH MULYANI (LPPM STIA Banten, 2016)
The purpose of this research was to examine empirically the correlation between discipline management and work motivation on job satisfaction among the facilitator at PNPM Mandiri in Lebak Regency. The subjects of this research were 80 facilitator selected as samples by using random sampling technique taken from the overall population of 100 facilitator. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The correlation technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the facilitator’s job satisfaction was positively affected by the discipline management and the work motivation in PNPM Mandiri in Lebak Regency, and the job satisfaction was simultaneous positively affected by the discipline management and the work motivation. The findings suggest that the variation of the job satisfaction of the facilitator might have been affected by the discipline management and the work motivation